High-Pressure Injection Injury Caused by Electronic Cigarette Explosion: A Case Report. Issue 2 (April 2017) - Foran, Ian; Oak, Nikhil R.; Meunier, Matthew J.
Abstract : Case: Electronic cigarettes are an increasingly popular and poorly regulated alternative to traditional cigarettes that deliver nicotine and other aerosolized substances to the user via a battery-powered atomizer. We report a case in which an electronic cigarette explosion resulted in a high-pressure injection injury of the finger. Conclusion: Explosions involving electronic cigarettes and similar handheld products should be treated as high-pressure injection injuries until proven otherwise. Radiographs are indispensable in the workup of these injuries. Because the true content of injected material cannot be determined with certainty, we recommend immediate surgical debridement, intravenous antibiotics, and close follow-up to observe the evolution of the injury.